Screening of aflatoxin M1 metabolite in urine samples of residents in Terengganu, Malaysia - Ahmad, Farah Nadira; Jamaluddin, Rosita; Mohd Esa, Norhaizan (Elsevier, 2020)
A study was conducted to screen the occurrence and level of aflatoxin M1 (AFM1) in urine samples of 206 urban and rural residents in Terengganu, Malaysia. The level of AFM1 was quantified by competitive enzyme-linked immune-absorbent assay (ELISA). Of the 206 samples, 84 were positive for AFM1 (40.8%) in a range of 0.07–5.53 ng/ml (mean = 0.589 ng/ml). Residents of Terengganu are moderately exposed to AFM1. Age, ethnicity, marital status and employment status were associated with urinary level of AFM1. Subjects aged 30 years and above, non-Malays, married, and those unemployed had significantly higher levels of urinary AFM1 (p < 0.05). Since aflatoxin is recognised as a potent-carcinogen for liver cancer and a continuous exposure to this toxin can be fatal, the present findings could provide a baseline for future studies where larger samples and more advanced techniques might be used to find the possible effects of the exposure of this toxin on the community's health.